Chemical biology tools to interrogate the roles of O-GlcNAc in immunity - Saha, Abhijit; Fernández-Tejada, Alberto (Frontiers in Immunology, 2023)
The O-linked β-N-acetylglucosamine (O-GlcNAc) glycosylation of proteins is an essential and dynamic post-translational modification in mammalian cells that is regulated by the action of two enzymes. O-GlcNAc transferase (OGT) incorporates this monosaccharide on serine/threonine residues, whereas O-GlcNAcase (OGA) removes it. This modification is found on thousands of intracellular proteins involved in vital cellular processes, both under physiological and pathological conditions. Aberrant expression of O-GlcNAc has been implicated in diseases such as Alzheimer, diabetes, and cancer, and growing evidence over the last decade has also revealed key implications of O-GlcNAcylation in immunity. While some key signaling pathways involving O-GlcNAcylation in immune cells have been discovered, a complete mechanistic understanding of how O-GlcNAcylated proteins function in the immune system remains elusive, partly because of the difficulties in mapping and quantifying O-GlcNAc sites. In this minireview, we discuss recent progress on chemical biology tools and approaches to investigate the role of O-GlcNAcylation in immune cells, with the intention of encouraging further research and developments in chemical glycoimmunology that can advance our understanding of O-GlcNAc in immunity.